A review of threshold responses of birds to landscape changes across the world. Issue 4 (18th November 2018) - Melo, Isabel; Ochoa‐Quintero, Jose Manuel; de Oliveira Roque, Fabio; Dalsgaard, Bo
Abstract: Identifying the threshold of habitat cover beyond which species of birds are locally lost is useful for understanding the biological consequences of landscape changes. However, there is little consensus regarding the impact of landscape changes on the likelihood of species extinctions. We conducted a literature search using Scopus and ISI Web of Knowledge databases to identify studies where bird species were used to estimate threshold responses to landscape changes. We obtained a list of 31 papers published from 1994 to 2018, with 24 studies conducted at temperate latitudes and seven in tropical regions. Nineteen studies were based on species‐level assessments, and investigators used a variety of response variables such as probability of detection and occurrence to detect threshold responses. Eight studies were based on communities, and species richness and abundance were primarily used to detect threshold responses. Four studies included both communities and species‐level assessments. Methods used to identify threshold responses varied among studies, but most relied on either regression models to visually identify values from graphs or piecewise regression to estimate a specific threshold value. Although the limited number of studies and their variety of approaches and methods prevented a formal meta‐analysis, we found that mean threshold responses in studies that reported either a range or a single threshold value were 27.9% at temperate latitudes (range = 1.3–90%; N = 11) and 33.6% at tropical latitudes (range = 20–50%; N = 7). Considering only studies where single threshold values were reported, the mean habitat cover threshold was 11% for studies conducted at temperate latitudes ( N = 3) and 29.5% for studies in the tropics ( N = 4). These crude estimates suggest that tropical species might be more susceptible to habitat loss than temperate species. Although application of the threshold concept is still controversial, the number of studies using this approach is increasing because the results of such studies may have direct application to conservation strategies and restoration of landscapes for bird conservation.